Match performance in young female basketball players: relationship with laboratory and field tests - Zaric, I.; Dopsaj, M.; Markovic, M. (International Journal of Performance Analysis in Sport, 2018)
The aim of this study was to examine the quantitative relationship between the results of laboratory and field tests assessing functional, metabolic and motor abilities and the match performances of young female basketball players. The research included the U16 female basketball players of the top three basketball clubs of the Serbian first under-16 league (N=30), (14.98 ± 0.68 yrs). The complex model method we applied included: laboratory and field testing and match performance analysis. The relations between the criterion and the system of predictors were determined by applying the multiple regression analysis, which defined the model of multiple relations and prediction. The research results have shown that the predictor variables are statistically significant, describing the criterion with 84.4% probability, meaning that there is a high multidimensional correlation between the results of laboratory and field tests and the match performance index. The practical application of this study implies a system of controlling the efficacy of the training process in the preparation stage, the selection and the creation of the model characteristics of functional, metabolic and motor abilities of young basketball players.